Technical executive’s organizational commitment at Malaysian oil & gas industry - Al R, Firend; Sofyan, Pamella (2015)
This research investigates the levels of organizational commitment among technical executive, identifies factors that influence organizational commitment in the Malaysian oil and gas industry, and examines the impact of organizational commitment on organizational performance.This research was conducted at Malaysia Marine and Heavy Engineering (MMHE).The framework adopted the three component-conceptualization of organizational commitment. Among the findings is that organizational commitment tends to influence stress level at work.A high level of effective commitment caused work stress to increase among st employee.